AGE AND GROWTH OF SPINY LOBSTER PANULIRUS POLYPHAGUS (HERBST) OF BOMBAY WATERS - Kagwade, P V (Indian Journal of Fisheries, 2011)
Age and growth of spiny lobster Panulirus polyphagus (Herbst) has beendetermined based on length-frequency method. Growth during the first 3 years isidentical in both sexes; 85 mm in the I year, 145 mm in II year and 205 mm inIII year. Thereafter the males grow faster than females; measuring 265 mm bythe end of IV year, 315 mm by the end of V year and 355 mm by the end ofVI yisar. Females measure 255 mm, 290 mm, 320 mm, 345 mm and 365 mmrespectively by the end of successive years IV to VIII.